Effect of point‐of‐care gastrointestinal ultrasound on decision‐making and management in inflammatory bowel disease. Issue 5 (22nd June 2021) - Friedman, Antony B.; Asthana, Anil; Knowles, Simon R.; Robbins, Aphra; Gibson, Peter R.
Summary: Background: Gastrointestinal ultrasound is increasingly used for point of care assessment of inflammatory bowel disease. Aims: To explore the utility of gastrointestinal ultrasound as a point‐of‐care assessment tool from the perspectives of the clinician and patient. Methods: A prospective, observational cohort study was designed utilising routine outpatient consultations. Adult patients with inflammatory bowel disease were allocated to receive gastrointestinal ultrasound or not at the discretion of their treating clinician. Patients completed self‐reported session experience questionnaires at study entry, immediately after their consultation, and 4 and 16 weeks later. Clinicians reported disease activity status, therapeutic decisions and clinical management. Results: Of 259 participants, mean age 40 (SD: 13) years, 54% male, 73 (28%) underwent ultrasound. Time since diagnosis was 9.2 (8.5) years (ultrasound) and 11.3 (9.2) years (no ultrasound). Immediately after ultrasound, patients who self‐reported active disease reported better understanding of all aspects of their disease and disease symptoms were more confident in their ability to make informed decisions about managing their disease and had improved knowledge domain scores compared with the non‐ultrasound group (all P < 0.05). Ultrasound had no influence over the patients' ability to manage their own healthcare but tended to be associated with transient improvement in medication adherence. After the ultrasound, the clinician's assessment of patient's disease activity changed in 22% (16/73) and management was altered in 56% (41/73) with anti‐inflammatory therapy escalated in 33. About 47% (23/49) patients with Crohn's disease had their medication changed in the ultrasound group, compared to only 22% (25/112) in the nonultrasound group ( P = 0.002). For patients with ulcerative colitis, medications were altered in 68% (15/22) compared to 26% (24/70) in the nonultrasound group ( P = 0.005) When stratified for disease activity, medication change was more likely in those having ultrasound ( P = 0.024). Conclusions: Point‐of‐care gastrointestinal ultrasound has the potential to enhance the clinical management of inflammatory bowel disease by contributing to clinician decision‐making and education of patients regarding their disease. Abstract : Point‐of‐care gastrointestinal ultrasound has the potential to enhance the clinical management of IBD by: 1. Facilitating clinician decision making, 2. Helping patients better understand their disease.